Placing Survival Above the Ideal of Motherhood: Experiences of Migratory Mourning of Migrant Mothers in Chile; [la Supervivencia por Sobre el Ideal de Maternidad: Experiencias de Duelo Migratorio de Las Madres Migrantes en Chile] - Castillo-Lobos, L; Contreras-Vasquez, L; Hermosilla-Aldea, E (Universidad Nacional de Lanos, 2023)
This article presents an approach to the phenomenon of migratory mourning of migrant mothers in Chile. Between 2021 and 2022, a qualitative exploratory study based on symbolic interactionism was carried out, in which semi-structured interviews were conducted with 39 migrant mothers of Venezuelan (18), Peruvian (11) and Haitian (9) origin. Based on a theoretically-informed thematic analysis, three analytical categories emerged: 1) the loss of social ties and distance to their place of origin; 2) expectations versus reality; and 3) the validation of overexertion. Migrant mothers express migratory mourning with varying levels of nuance depending on their country of origin, and to a greater or lesser degree signify their experiences in terms of uprooting and the absence of support networks, which they identify as the main cause of the sadness they experience on a daily basis. This sadness increases when they negotiate their ideals regarding the upbringing of their sons and daughters in favor of material subsistence in order to achieve the goals of a better life, and for which they justify overexertion as a strategy for improvement. These pressures bring with them psychological and physical consequences and interfere with their processes of migratory mourning, compromising their mental health and that of their children. © 2023, Esta obra está bajo una licencia Creative Commons Atribución 4.0 Internacional (CC BY 4.0). https://creativecommons.org/licenses/by/4.0/.